A Review of Energy Dissipater as a Mitigation for Dam Risk Management - Melan A.; Syamsir A.; Zawawi M.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Dams; Flow velocity; Hydraulic jump; Risk management; Spillways; Stilling basins; Block ramp; Current safety; Dam risk management; Energy dissipaters; Flip bucket; Heavy rainfall; Risks management; Safety criterion; Ski-jump bucket; Stepped spillways; Energy dissipation